Metodología para la aplicaciónde una auditoría financiera para la empresa comercial Eléctrico Santana ubicada en el Distrito Metropolitano de Quito - Alquinga Quinchiguano, Grace Tatiana (2015)
This project of this thesis represents a practical application of a financial audit at Comercial Eléctrico Santana., Whose activity is focused on the commercialization of electrical equipment. The results of the financial statements of the company Comercial Eléctrico Santana allow determining the reasonableness of the financial statements of the company and seeing if they are manufactured under regulations and laws. The first chapter includes an overview of the financial audit, where the terms, concepts and basic procedures deepens, which will feed the theoretical framework of this study. In addition we will correct the conceptualization, guiding on how this research will take place, this information will allow us basic concepts that are useful to the study that we will. The second chapter covers the generalities of the company to be audited and the environment in general terms your organization stands out among others its rationale and history from the beginning of the operation. The third chapter details and conceptualizes the methodology to be applied, it is how the audit process is developed, taking into account the phases, procedures and tools, techniques, testing, working papers and types of views that could result upon examination of the financial statements. The fourth chapter is the practical preparation for the audit; including the whole process of it, with the results they will be documented in the report supported with a personal opinion and a management letter.